ЭЛЕКРОФИЗИОЛОГИЧЕСКОЕ ИССЛЕДОВАНИЕ ВАРИАБЕЛЬНОСТИ СЕРДЕЧНОГО РИТМА И ПАРАМЕТРОВ ВНЕШНЕГО ДЫХАНИЯ ПРИ ОТРАВЛЕНИИ ФТОРАЦЕТАМИДОМ (Experimental biology, 2015)
Acute poisoning by fluoroacetamide, which disturb the tricarbonic acids cicle, provoke significate change of cardiovascular and respiratory systems activity. After shot timed increase of a role humoromethobolic and sympaticactivity had seen noted increase of parasimpatic influence on the heart rate variability.
Keywords: heart rate variability